Pengaruh ROA Dan ROE terhadap Harga Saham pada Perusahaan Sektor Perbankan yang Terdaftar di BEI Tahun 2022-2024 - Aprianto, Aprianto; Maithy, Sifera Patricia (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study analyzes the effect of Return on Assets (ROA) and Return on Equity (ROE) on the stock prices of banking sector companies listed on the Indonesia Stock Exchange during 2022 to 2024. Using a quantitative approach with multiple linear regression analysis on secondary data from annual financial statements, the results show that ROA has a positive and significant effect on stock prices, while ROE does not show a significant impact. These findings provide insights for investors and company management in making investment decisions amid economic uncertainty.